THE IMAGE OF WOMEN IN THE ARABIC LANGUAGE TEXTBOOK FOR THE PRIMARY SECOND GRADE IN JORDAN - Otoom, Kamel Ali Sulieman (European Scientific Journal, ESJ, 2014)
This study is aimed at investigating the image of women exemplified by the roles and values and the nature of the dominant discourse on the language in "the Arabic language" book, for the primary second grade in Jordan compared to the image of men, through the use of the content analysis methodology. The Study population and the sample of the study is the book of Arabic language for the primary second grade. As its tool for a couple of questions, the first and second were two lists: the first for roles and the second for values. The third question on the linguistic discourse has been answered by the analysis of expressive vocabulary for sex, and has been placed into three categories, namely: expressive vocabulary for males, the mouthpiece of the female, and neutral, which has been used to achieve the tool for validity and reliability. The study found that women appeared in (41) role versus (74) role for men; however, most roles of women which are often repeated are the role of the mother and the daughter and the role of the pupil and a teacher and also the role of a friend. However, woman appeared only once as a researcher, as a farmer, a painter and a director. Men appeared in a series of playing the role of a father and son, a brother and uncle and a friend, a soldier, a doctor and a pharmacist, poet and a farmer. Women usually possess values such as compassion, humility and care for the family, honoring the parents of the man and maintaining cleanliness, while the men emerged clearly with standing values of courage, the preservation of time, generosity, and sacrifice, independence, and leadership, and provides security and advice. The discourse of linguistic may be greater than the male rate (56%), while the female discourse only gets to a rate of (5.4%), and the remainder gives a neutral speech.